2012
DOI: 10.1161/circulationaha.111.055939
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score for Predicting Long-Term Mortality After Coronary Artery Bypass Graft Surgery

Abstract: Background No simplified bedside risk scores have been created to predict long-term mortality after coronary artery bypass graft (CABG) surgery. Methods and Results The New York State’s Cardiac Surgery Reporting System was used to identify 8,597 patients who underwent isolated CABG surgery in July-December 2000. The National Death Index was used to ascertain patients’ vital status through December 31, 2007. A Cox proportional hazards model was fit to predict death following CABG surgery using pre-procedural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 20 publications
(31 reference statements)
6
74
0
10
Order By: Relevance
“…Upon closer review, the Hannan model was seen to be most accurate for risk predictions for the subgroup of patients ≤50 years of age. This supports Wu et al's statement that their model is useful “…for informed consent and as an aid in determining treatment choice,”6 but suggests the model's greatest strength may lie in its accuracy in providing long‐term mortality estimates for younger or sicker patients. The Hannan model was not designed to be specific for cardiac‐related deaths only; therefore, no comment can be made on the likely distribution of non‐cardiac versus cardiac‐related causes of death in our patient sample.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Upon closer review, the Hannan model was seen to be most accurate for risk predictions for the subgroup of patients ≤50 years of age. This supports Wu et al's statement that their model is useful “…for informed consent and as an aid in determining treatment choice,”6 but suggests the model's greatest strength may lie in its accuracy in providing long‐term mortality estimates for younger or sicker patients. The Hannan model was not designed to be specific for cardiac‐related deaths only; therefore, no comment can be made on the likely distribution of non‐cardiac versus cardiac‐related causes of death in our patient sample.…”
Section: Discussionsupporting
confidence: 68%
“…No confidence intervals were calculated for the Hannan O/E ratios, however, as the values of these confidence intervals were not published with the point estimates given in the Wu et al publication 6. For further reference, all observed mortality proportions and models' predicted mortality probabilities are listed in Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Wigfield et al (14) also documented similar results, but they reported an increase in rates of complications like prolonged ventilation and acute renal failure without hemodialysis. Conversely, Wu et al (15) reported that obesity was an independent risk factor for mortality in long term followup after coronary bypass surgery. We documented that the mortality rates were similar in both groups.…”
Section: Discussionmentioning
confidence: 98%
“…Besonders deutlich wird dies am stark erhöhten kardiovaskulären Risiko bei Patienten mit chronischer Nierenkrankheit. Für kardiovaskuläre Erkrankungen stellt die chronische Nierenkrankheit einen der wesentlichen Risikofaktoren noch vor dem Diabetes mellitus dar [1]. Allerdings können auch Funktionsstörungen anderer Organe die Funktion der Niere beeinträchtigen.…”
Section: Die Nieren Im Umfeld Von Organschädenunclassified